Instructors' understanding of and responses to student privacy in the datafied classroom. Issue 1 (22nd October 2020) - VanScoy, Amy; Jones, Kyle M. L.; Bright, Kawanna; Harding, Alison
Abstract: The prevalence of educational technology has led to the creation of the "datafied classroom, " a sociotechnical environment captured in and treated as analyzable data for educational data mining and learning analytics practices. This "datafied classroom" presents risks, namely to student privacy. There is a need to better understand how faculty perceive student privacy issues and strategize to address them in practice. This poster reports emerging findings from an IMLS‐funded study that surveyed 502 instructors representing colleges and universities in the United States. The survey captured instructor knowledge of, attitudes and values about, and instructional design experiences with student privacy issues.